The Relationship between Microbial Communities in Coffee Fermentation and Aroma with Metabolite Attributes of Finished Products - Tatsaporn Todhanakasem; Ngo Van Tai; Soisuda Pornpukdeewattana; Theppanya Charoenrat; Briana M. Young; Songsak Wattanachaisaereekul (My University, 2024)
Coffee is a critical agricultural commodity and is used to produce premium beverages enjoyed by people worldwide. The microbiome of coffee beans has proven to be an essential tool that improves the flavor profile of coffee by creating aromatic flavor compounds through natural fermentation. This study investigated the natural microbial consortium during the wet process fermentation of coffee onsite in Thailand in order to identify the correlation between microbial diversity and biochemical characteristics including flavor, aroma, and metabolic attributes. Our study found 64 genera of bacteria and 59 genera of yeast/fungi present during the fermentation process. Group of microbes, mainly yeast and lactic acid bacteria, that predominated in the process were significantly correlated with preferable flavor and aroma compounds, including linalyl formate, linalool, cis-isoeugenol, trans-geraniol, and (-)-isopulegol. Some of the detected metabolites were found to be active compounds which could play a role in health.
Keywords: Coffee research and impacts